THE MANAGEMENT OF SPENT CATALYST IN RCC/FCC UNITS IN ASEAN REFINERIES - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 2005)
Catalytic cracking processes convert heavy feed- stock (heavy distillate, residue) into gasoline and light cycle stock for middle distillate components. Due to high impurity of feedstock and limited operating condition of catalyst regeneration, fresh catalyst must be added to replace a portion of spent catalyst continously, to maintain the activity of equilibrium catalyst in the reactor. Spent catalyst must be disposed properly so that it does not cause hazard or environmental concern. A survey was conducted on the management of spent catalyst in RCC/FCC unit in ASEAN refineries as an ASCOPE Technical Committee work programme for 1996. Indonesia was tasked as the Coordinator with the support of Member Countries. The Coordinator for each Member Country is listed in the Table 1. This paper discusses briefly catalytic cracking process, deactivation of cracking catalyst and the management of spent cata- lyst in RCC/FCC unitsÂ